(untitled) (Analysis of International Sciences, 2024)
In this article, the author examines the positive effects of World Trade Organization (WTO) membership on the digital economy. The World Trade Organization is an international organization aimed at developing global trade and reducing trade barriers between countries. Countries make several compelling arguments outlining the benefits that WTO membership can enjoy for their digital economy. First, they argue that WTO membership provides a framework for establishing clear and predictable rules for digital trade. This framework will help reduce uncertainties and encourage investment in the digital sector through legal protection of intellectual property rights and enforcement of e-commerce regulations. In conclusion, this article sheds light on how joining the World Trade Organization can positively impact a country’s digital economy. It states that membership creates a favorable environment for business development by establishing clear rules, facilitating market access and ensuring active participation in global digital trade negotiations. However, to maximize the benefits of WTO membership for the digital economy, it is important to consider potential challenges and effectively address them.